Analisis Kapasitas Short Message Service (SMS) dan Probability Packet Loss pada Sistem Peringatan Dini Nirkabel di Tangki Fluida - Melvi, Melvi; Ulvan, Ardian; Aditama, Aris; Batubara, Mona Arif Muda (Penerbit Goodwood, 2023)
Purpose: In this research a wireless early warning system is designed and examines how to overcome communication errors or delays in information received by operators by analyzing traffic and Blocking Probability SMS (Short Massege Service) in wireless early warning systems on fluid tanks. Methodology: System testing uses the FC 37 sensor as a fluid sensor (which includes electrolytes or can conduct electric current). Results: This early warning system works well and works at a droplet volume of ± 0.5 ml. Based on the calculation of SMS Blocking Probability based on the increasing number of SMS subscribers, the Blocking Probability also increases. For the number of SMS 8448 subscribers the Blocking Probability SMS is 0.0093% and for the number of SMS 11520 subscribers the Blocking Probability SMS is 0.1719%. The Probability of Packet Loss is influenced by the Probability of BER. Probability BER calculation using the modulation used, namely 16-QAM (with a code rate of ½ and ¾) and 64-QAM (with a code rate of 2/3 and ¾) is influenced by the distance of the UE to the BTS. This distance has an effect because the BER Probability calculation uses the Walfish-Ikegami propagation model to calculate Pathloss. At a distance of UE and BTS 0.2 km Probability Packet Loss using 16-QAM ½ 2.55 x 10-14 modulation, 16-QAM ¾ 1.14 x 10-14 modulation, 64-QAM 2/3 3.05 x 10 modulation -9, and 64-QAM ¾ 2.94 x 10-9. The 16-QAM Packet Loss value is smaller than the 64-QAM because the bit values used are different, 16-QAM uses 4 bits while 64-QAM uses 6 bits.